Exergy methods for commercial aircraft integrating the laws of thermodynamics into all disciplines of aircraft design. - Hayes, David (Cranfield University, 2018)
As a consequence of practicalities, work share and difficulties in designing complex aerospace systems, there has been historical segregation of sub-systems in aircraft design. This methodology has proved successful for conventional swept wing aircraft configurations, as the sub-systems are only loosely integrated with one another. This results in discipline-specific performance, loss and optimization metrics being developed at sub-system level, which are not clearly linked to the overall system performance or objective. To meet social, economic and environmental needs, the next generation of aircraft require revolutionary concepts, which tend to be far more integrated, similar to military vehicles. Thus, performance, loss and optimization metrics need to be considered at system level, in order to account for the interactions between competing engineering disciplines. This thesis advocates an alternative systems engineering approach to developing future commercial aircraft, where the universal thermodynamic metrics energy and entropy are coupled to provide a holistic performance, loss and optimization metric for all aircraft disciplines. The method known as exergy analysis has been applied in the development of propulsion systems, but is sparsely applied in other aerospace disciplines. Applying the laws of thermodynamics to all aircraft sub-systems can seem obscure, especially in mature disciplines such as aerodynamics where energy may only be considered implicitly. Along with conventional configurations, this thesis studies a conceptual highly integrated High Aspect Ratio Wing (HARW) aircraft with morphing wing-tips, where the extended wingspan improves aerodynamic performance but as a consequence the wings have greater flexibility. Morphing is not a widely proliferated technology primarily due to the conservative approach to civil aircraft design, but original equipment manufacturers also struggle to demonstrate how the morphing effectiveness on a scale model can be scaled up to a full size aircraft. This thesis shows a clear contribution to knowledge in extending the current exergy methodology by investigating flight dynamic exergy analysis, and its application to morphing technologies for large commercial aircraft, evaluating the aerodynamic and aeroelastic contribution to an aircraft’s overall exergy use. To achieve this, each node of the Collar’s triangle [27] is evaluated using the exergy metric. In the absence of an open-source code, a non-linear structural code designated the Beam Reduction (BeaR ) model, has been written to study the structural dynamics of an airframe written in MSC Nastran format within a MATLAB® / Simulink® environment. To facilitate the study of flight dynamics, a bespoke Prandtl-Glauert aerodynamics model with an exergy post-processing script has been developed. Static and dynamic aeroelastic effects were studied through a coupling of the aforementioned structure and aerodynamic exergy based models. One of the main barriers to applying exergy analysis to commercial aircraft is gaining acceptance of a novel methodology in disciplines with entrenched practices. An example being in aerodynamic design, where the force balance approach is the established analysis method, yet exergy analysis requires the engineer to consider an alternative view of the aerodynamics as a system that uses and converts energy. To counter this, the thesis shows the capability and benefits of exergy analysis over conventional analysis techniques. This is emphasised in the comparison of using exergy based methods or the Breguet Range Equation for assessing the performance benefit of morphing wing extensions, where both methods provide the same top level conclusion, but exergy provides additional insight into the system the Breguet analysis can not.
Keywords: Exergy analysis; high aspect ratio wing (HARW); flight dynamic exergy analysis; aeroelastic effects; aerodynamic exergy; thermodynamics